2007
DOI: 10.1016/j.jmgm.2007.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-phosphate pKa and binding constants: Intramolecular and intermolecular influences

Abstract: The dissociation constant for an ionizable ligand binding to a receptor is dependent on its charge and therefore on its environmentally-influenced pK a value. The pK a values of sphingosine 1-phosphate (S1P) were studied computationally in the context of the wild type S1P 1 receptor and the following mutants: E3.29Q, E3.29A, and K5.38A. Calculated pK a values indicate that S1P binds to S1P 1 and its site mutants with a total charge of −1, including a +1 charge on the ammonium group and a −2 charge on the phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 72 publications
(25 reference statements)
5
15
0
Order By: Relevance
“…LPA and sphingosine-1-phosphate (S1P) are important signaling molecules that bind and activate G-protein-coupled receptors (GPCRs), located in the plasmamembrane and nuclear membrane of cells. This is exactly what recent work by Tigyi and Parrill on the binding of S1P to the S1P 1 receptor showed (Naor et al 2007). Interestingly, the results described above would suggest that LPA and S1P bind to their receptors in a di-anionic form.…”
Section: Computational and Experimental Evidence For The Electrostatisupporting
confidence: 88%
See 2 more Smart Citations
“…LPA and sphingosine-1-phosphate (S1P) are important signaling molecules that bind and activate G-protein-coupled receptors (GPCRs), located in the plasmamembrane and nuclear membrane of cells. This is exactly what recent work by Tigyi and Parrill on the binding of S1P to the S1P 1 receptor showed (Naor et al 2007). Interestingly, the results described above would suggest that LPA and S1P bind to their receptors in a di-anionic form.…”
Section: Computational and Experimental Evidence For The Electrostatisupporting
confidence: 88%
“…The binding of LPA and S1P to their respective GPCRs critically depends on the phosphomonoester headgroup (Lynch and Macdonald 2002;Sardar et al 2002), and the phosphate-binding region of the LPA receptors all contain two conserved basic residues (one arginine and one lysine residue, (Sardar et al 2002)). Importantly, this work also revealed that the intramolecular hydrogen bond between the hydroxyl group in the backbone of S1P and the phosphomonoester stabilizes the deprotonated form of S1P, exactly what was observed experimentally for the related lipid ceramide-1-phosphate (Cer-1-P; Kooijman et al 2008;Naor et al 2007). This is exactly what recent work by Tigyi and Parrill on the binding of S1P to the S1P 1 receptor showed (Naor et al 2007).…”
Section: Computational and Experimental Evidence For The Electrostatisupporting
confidence: 80%
See 1 more Smart Citation
“…They illustrated their findings with a model of the ligand-receptor complex constructed on early rhodopsin model based on distance geometry calculations with hydrogen bonding constraints [51]. Those three residues were also shown as binding S1P in S1P 1 binding site in more recent paper of the same group [52]. The crystal structure of S1P 1 receptor with antagonist ML056 can verify to some extent those findings.…”
Section: Resultsmentioning
confidence: 75%
“…These results contradict an alternative model of S1P complexed with S1P 4 that suggested interactions predominantly in the extracellular loops [98]. Further modeling and mutagenesis studies identified W4.64 and K5.38 as positions that show variable importance in the S1P receptors [93,101]. Investigations of both LPA and S1P receptor indicate that a cationic residue in TM7 is often, but not universally, involved in ligand recognition [40,88,93].…”
Section: Modeling Lysophospholipid Interactions With Gpcr-mentioning
confidence: 62%